Oxidation of acetaminophen by fluidized-bed Fenton process optimization and kinetic study - Briones, Rowena M. (2011)
One of the most frequently used over-the-counter analgesic and antipyretic is acetaminophen (ACT). This drug finds its way into effluent wastewaters in concentrations that still pose an environmental threat even after conventional treatment methods. This study demonstrates the effectiveness of fluidized-bed Fenton process in the degradation of synthetic acetominophen wastewater. The effect of initial conditions such as pH, Fe²+ and H₂O₂ concentrations and the presence of organic acids were examined. Box-Behnken experimental design was employed to optimize initial pH, Fe²+ and H₂O₂ concentrations. Optimization of initial operating conditions gave the best removal efficiency at pH =3.22, [Fe²+]= 0;06 mM and [H₂O₂]=19.87 mM. Verification studies resulted in 97.83% ACT removal with an initial rate of 0.234 mM/min. Chemical oxygen demamd (COD) and total organic carbon (TOC) removals of 38.18% and 25.5%, respectively, were achieved. Simple reaction kinetics was used to model the first 20-40 minutes of reaction. Pseudo 2nd order was found to be the best fit for the data. Intermediates were also identified in this study using solid phase microextraction gas chromatography/mass spectroscopy (SPME-GC/MS) and a reaction pathway was proposed.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Acetaminophen; Fluidization; Sewage -- Purification -- Oxidation